Conceptualizing business process standardization: A review and synthesis - Kanika Goel; Wasana Bandara; Guy Gable (Schmalenbach Journal of Business Research (SBUR), 2023)
"Business Process Standardization" (BPS) is a practice intended to achieve consistency across underlying organizational processes, in support of service-delivery excellence and optimization of costs and benefits. Given the growing importance of BPS, there is need in both research and practice for clearer conceptual understanding of the notion. Following a systematic literature review approach, prior work on Business Process Standardization is synthesized and extended using tool-supported qualitative data analysis techniques, to derive an evidence-based, holistic conceptualization of BPS. We distil seven stages of BPS execution, propose a refined definition for BPS, and identify measures that gauge the several conceptual themes of BPS. The findings provide solid theoretical foundations, and practicable guidelines for future BPS researchers and practitioners.
Keywords: 650; Business Process Standardization; Business Process Management; Conceptualization; Definition; Measures; Structured Literature Review